2022
DOI: 10.1177/1420326x211061111
|View full text |Cite
|
Sign up to set email alerts
|

Simple correlations between point daylight factor, average daylight factor and vertical daylight factor under all sky conditions and building design implications

Abstract: The customary method for calculating daylight illuminance in a building is the daylight factor approach, which is assumed under the conventional overcast sky. However, such an approach is not flexible enough to predict diffuse illuminance in the presence of non-overcast skies. The daylight factor is invariant to building orientation and cannot take realistic and time-varying climatic conditions into account. Daylight in buildings is estimated using computer simulation techniques. However, full-scale computer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…There are simple correlations between PDF and VDF under all sky conditions [ 57 ]. The ratio of PDF to VDF can be computed using a number of room parameters and the configuration factor for a vertical rectangle plane to a horizontal point [ 24 ].…”
Section: Results Analysis and Design Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are simple correlations between PDF and VDF under all sky conditions [ 57 ]. The ratio of PDF to VDF can be computed using a number of room parameters and the configuration factor for a vertical rectangle plane to a horizontal point [ 24 ].…”
Section: Results Analysis and Design Implicationsmentioning
confidence: 99%
“…The primary drawback for closed-loop daylight-linked switching control is the sudden and quite often of lamp fittings turning on and off when the sensed daylight plus electric lighting is merely greater than the illuminance set point. The daylight illuminance monitored at the reference point is the recorded vertical daylight illuminance (VDI) times the ratio of PDF to VDF which is well correlated [ 57 ]. Further study for open-loop daylight-linked lighting controls based on such technique will be examined in near future.…”
Section: Results Analysis and Design Implicationsmentioning
confidence: 99%
“…Precisely, it defines the percentage of floor area that receives the level illuminance for a standard percentage (e.g. 50%) of the annual working hours [37]. A more detailed definition is the percentage of an analysis area (work plane) that meets the minimum daylight illuminance level (300 lux) for a required fraction of the operating hours per year.…”
Section: Phase Ii; Preliminary Simulationmentioning
confidence: 99%
“…For example, the requested horizontal illuminance and DF for classrooms in Daylight Zone 4 are 450 lx and 3.3%, respectively. 13 One way of advancing the Chinese Standard for daylight is to examine and employ international vertical eye illuminance that has been explored, proposed and validated by global researchers for years [19][20][21] as well as CBDMs. However, one important factor that potentially influences the global generalization of daylighting design metrics is socioenvironmental contexts, defined as 'the climate and habitat (interior and exterior) to which a person has acclimatized and their behaviour and expectations towards these elements' by Pierson et al 22 Two types of studies have demonstrated the impact of socio-environmental context upon subjective daylighting evaluations: indirect ones and direct ones.…”
Section: Introductionmentioning
confidence: 99%